Effectiveness of centralized quarantine for close contacts' close contacts: an evaluation on a Delta variant-induced local COVID-19 outbreak - Jin-ren PAN; En-fu CHEN (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo evaluate the effectiveness of centralized quarantine for close contacts' close contacts (sub-contacts) in coronavirus disease 2019 (COVID-19) epidemic. MethodsThe definition of sub-contacts for this study is based on the State Council's Joint Prevention and Control Protocol for Prevention and Control of COVID-19 (Edition 8). The information on 8 192 sub-contacts were extracted from the dataset of a COVID-19 epidemic caused by a Delta variant of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in a district of Shaoxing city, Zhejiang province in December 2021. All the sub-contacts were followed retrospectively; the epidemiologic survey reports of all sub-contacts with subsequent SARS-CoV-2 infection and the infected sub-contacts' related cases/close contacts were reviewed and analyzed. The effect of the centralized quarantine for the sub-contacts was assessed as effective, ineffective, adverse effect, and uncertain, respectively based on outcomes (SARS-CoV-2 infection incidence) of follow ups on both the close contacts and the sub-contacts. ResultsTotally 387 confirmed SARS-CoV-2 infections were reported in the epidemic and averagely 21 sub-contacts were associated with one confirmed infection in the epidemic. Of all the sub-contacts, 99.8% were negative for SARS-CoV-2 nucleic acid in multiple successive PCR tests, suggesting an unnecessity of the centralized quarantine. By the end of the retrospective follow-up period, 18 (0.2%) of the sub-contacts were with positive result of SARS-CoV-2 nucleic acid test and all the positive sub-contacts were associated close contacts' familial cohabitants. Among the 18 SARS-CoV-2 nucleic acid positive sub-contacts, 9 were identified being with the associated close contacts never being positive for SARS-CoV-2 nucleic acid test throughout the retrospective follow-up period, indicating that the sub-contacts might be infected during the transfer or centralized quarantine period. The analysis results suggest that among the 18 SARS-CoV-2 nucleic acid positive sub-contacts, the centralized quarantine is not necessary for all the sub-contacts, ineffective for 3 (16.7%) sub-contacts, with an adverse effect for 9 (50.0%) sub-contacts, and with uncertain effect for 6 (33.3%) sub-contacts, respectively. ConclusionThe analysis showed no evidence of positive control effect of centralized quarantine for sub-contacts in a Delta variant induced COVID-19 epidemic but that a few sub-contacts could be infected in the process of transfer and centralized quarantine. The analysis results suggest that centralized quarantine for close contacts' close contacts could be suspended and more studies are needed for effective management on sub-contacts, such as home quarantine in containment of COVID-19 epidemic.